The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0104-42302003000400026
|View full text |Cite
|
Sign up to set email alerts
|

O processo de consentimento livre e esclarecido em pesquisa: uma nova abordagem

Abstract: These results evidence the possibility to inform collectively the research subjects when getting the Informed Consent in those projects where this choice is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
13

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 0 publications
0
13
0
13
Order By: Relevance
“…14,22 Subjects should understand procedures, risks, discomforts, benefi ts and rights involved in their participation in the research. 11 However, some studies have shown limited knowledge about the research among individuals that had consented to participate, 13 which may be due to the research subjects' conscious choice to disregard information, or to failures in the communication process. 13 For communication to be effective, it is necessary to adopt a model that values both the transmitted content and the speech act, that is, how the actors involved in the communication act transmit proposals, understand them and respond to them.…”
Section: Right To Autonomy and Informed Consentmentioning
confidence: 99%
See 1 more Smart Citation
“…14,22 Subjects should understand procedures, risks, discomforts, benefi ts and rights involved in their participation in the research. 11 However, some studies have shown limited knowledge about the research among individuals that had consented to participate, 13 which may be due to the research subjects' conscious choice to disregard information, or to failures in the communication process. 13 For communication to be effective, it is necessary to adopt a model that values both the transmitted content and the speech act, that is, how the actors involved in the communication act transmit proposals, understand them and respond to them.…”
Section: Right To Autonomy and Informed Consentmentioning
confidence: 99%
“…Goldim et al, 11 using empirical data, suggest that the collective transmission of information can be effective in the recollection of information that is necessary to the informed consent.…”
Section: Right To Autonomy and Informed Consentmentioning
confidence: 99%
“…By return mail and phone calls from family members, we were informed that three more patients had died. The time course of return of the forms ranged from 2 to 89 days [median: 10 days; mean: 18 days; 95% confidence interval (CI) [14][15][16][17][18][19][20][21][22], considering a median follow-up of 331 days (mean: 323 days, 95%CI 314-331).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the lack of face-to-face interaction may have minimized the chance of coercion, which can sometimes occur, albeit unintentionally. 19,20 Nevertheless, some patients contacted the researchers by visiting the Institution, calling them or sending written messages.…”
Section: Resultsmentioning
confidence: 99%
“…Another tool suggested to increase the level of understanding by those invited to participate is their collective communication of the information 48 . This resource consists of explaining the research information of interest to the team, seeking to foster disinhibition and decreased embarrassment, and helping to clarify doubts and particularities.…”
Section: Final Considerationsmentioning
confidence: 99%